Study on clinical diseases and disorders of cattle and goat at Gopalgonj District in Bangladesh - Khan, Nidra Boti; Pal, Dipa Rani; Mollah, Mohammad Lalmoddin (Asian Journal of Medical and Biological Research, 2018)
This clinical study was undertaken at the sadar Upazilla Livestock Office, Gopalgonj, Bangladesh to determine the general clinical prevalence of clinical diseases and disorders in cattle and goats during the study period from September to December 2016. Total animals were 105, among them cattle were 60 and goats were 45. Diagnosis was performed on the basis of general examination, physical examination and clinical examination. Clinical examinations were detected 60 (48.38% of total animals) different types of diseases and disorders in cattle. Whereas fever 3, anorexia 5, bloat 2, dysentery 3, diarrhoea 4, fascioliasis 2, myiasis 5, FMD 2, papillomatosis 2, ephemeral fever 3, pneumonia 5, mastitis 4, black quarter 1 were recorded. Age wise occurrence in young and adult cattle were 35 (58.33%) & 25 (41.66%) respectively. In goat 45 (36.29% of total animal) different types of diseases and disorders were found. Whereas fever 4, anorexia 4, bloat 1, dysentery 2, diarrhoea 3, corneal opacity 2, mange 3, myiasis 4, PPR 10, pneumonia 8, tetanus 1, mastitis 3 were recorded. Age wise occurrence in young and adult goat were 20 (44.44%) and 15 (33.33%) respectively. Diseases and disorders of cattle and goats which were recorded more or less present in both young and adult animals but some of the specific diseases and disorders were in animals due to age susceptibility such as black quarter in young cattle and PPR in goat. From this study it can be said that proper vaccination, treatment and management should be given to minimize the diseases and disorders of cattle and goat. Asian J. Med. Biol. Res. December 2017, 3(4): 412-418